Effectiveness of DL (Discovery Learning) Learning Model Integrated IDA (Identify, Explore, Actualize) Assisted by CET Media (Chemo Edutainment) on The Material of The Mole Concept - Dhakiorh, Dhakiroh; Sumarni, Woro; Prasetyo, Agung Tri (Universitas Negeri Semarang, 2024)
This study aims to analyze the effectiveness of the IDA integrated DL learning model assisted by Nearpod application CET media on the material of the mole concept in increasing interest and learning outcomes of the mole concept. This research is an R and D (Research and Development) research. The design used is ADDIE including (1) analysis (needs analysis, infrastructure analysis, determining scope, determining boundaries and sources); (2) design (determining innovative ideas, making the syntax of the IDA-integrated DL learning model assisted by Nearpod CET media, making learning devices (Teaching Modules, LKPD and evaluation instruments, making Nearpod CET media prototypes on mole concept material); (3) development (validation of the syntax of the IDA-integrated DL learning model assisted by Nearpod application CET media, small-scale trials); (4) implementation (large-scale trials, tests) and (5) evaluation. Data collection techniques are learning outcomes test, observation, interview, and Likert scale of interest. Data analysis techniques are instrument validation, interest data analysis and learning outcomes. The data obtained are the results of validation of media experts and material experts, responses of students and teachers on small-scale trials, pretest and posttest results of students on large-scale trials. The results showed the effectiveness of the IDA-integrated DL learning model assisted by Nearpod CET on the mole concept material in the experimental class for learning outcomes N-gain value of 0.8148 has a high category. For learning interest, the N-gain value of 0.7725 has a high category.